Folate-targeted immunotherapies: Passive and active strategies for cancer. (February 2019) - Farran, Batoul; Pavitra, Eluri; Kasa, Prameswari; Peela, Sujatha; Rama Raju, Ganji Seeta; Nagaraju, Ganji Purnachandra
Graphical abstract: Highlights: The transport protein FRα is upregulated in various solid malignancies. FRα is immunogenic and is a suitable target for immunotherapeutic drugs in cancer. Passive anti-FRα immunotherapies include monoclonal antibodies. Active anti-FRα immunotherapies include CART, folate-associated haptens and vaccines. Abstract: The glycoprotein FRα is a membrane-attached transport protein that is shielded from the immune system in healthy cells. However, it is upregulated in various malignancies, involved in cancer development and is also immunogenic. Furthermore, FRα is a tumor-associated antigen endowed with unique properties, thus rendering it a suitable target for immunotherapeutic development in cancer. Various anti- FRα immunotherapeutic strategies are thus currently being developed and clinically assessed for the treatment of various solid tumors. These approaches include passive anti-FRα immunotherapies, such as monoclonal antibodies, or active immunotherapies, such as CART, folate haptens and vaccines. In this review, we will explore the advances in the field of FRα-based immune therapies and discuss both their successes and shortcomings in the clinical setting.